Williams–Beuren syndrome in diverse populations - Kruszka, Paul; Porras, Antonio R.; de Souza, Deise Helena [UNESP]; Moresco, Angélica; Huckstadt, Victoria; Gill, Ashleigh D.; Boyle, Alec P.; Hu, Tommy; Addissie, Yonit A.; Mok, Gary T. K.; Tekendo-Ngongang, Cedrik; Fieggen, Karen; et al. (Wiley, 2018)
Williams–Beuren syndrome (WBS) is a common microdeletion syndrome characterized by a 1.5Mb deletion in 7q11.23. The phenotype of WBS has been well described in populations of European descent with not as much attention given to other ethnicities. In this study, individuals with WBS from diverse populations were assessed clinically and by facial analysis technology. Clinical data and images from 137 individuals with WBS were found in 19 countries with an average age of 11 years and female gender of 45%. The most common clinical phenotype elements were periorbital fullness and intellectual disability which were present in greater than 90% of our cohort. Additionally, 75% or greater of all individuals with WBS had malar flattening, long philtrum, wide mouth, and small jaw. Using facial analysis technology, we compared 286 Asian, African, Caucasian, and Latin American individuals with WBS with 286 gender and age matched controls and found that the accuracy to discriminate between WBS and controls was 0.90 when the entire cohort was evaluated concurrently. The test accuracy of the facial recognition technology increased significantly when the cohort was analyzed by specific ethnic population (P-value < 0.001 for all comparisons), with accuracies for Caucasian, African, Asian, and Latin American groups of 0.92, 0.96, 0.92, and 0.93, respectively. In summary, we present consistent clinical findings from global populations with WBS and demonstrate how facial analysis technology can support clinicians in making accurate WBS diagnoses.
Keywords: Africa; Asia; diverse populations; facial analysis technology; Latin America; Middle East; syndrome; Williams; Williams–Beuren